X-Ray Scattering 2017
DOI: 10.5772/64877
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Incidence Small Angle X-Ray Scattering as a Tool for In- Situ Time-Resolved Studies

Abstract: With the advent of third-generation synchrotron sources and the development of fast two-dimensional X-ray detectors, X-ray scattering has become an invaluable tool for insitu time-resolved experiments. In the case of thin films, grazing incidence small angle X-ray scattering (GISAXS) constitutes a powerful technique to extract morphological information not only of the thin film surface but also of buried structures with statistical relevance. Thus, recently in-situ GISAXS experiments with subsecond time resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…107 In a study of highly proton-ordered water structures on oxygen pre-covered Ru(0001) it could be shown that the atomic oxygen and the oxygen from water form a (2 Â 2) surface reconstruction, which however, is broken by the hydrogen to give a (2 Â 4) surface reconstruction: while LEED measured a (2 Â 2), HAS measured a (2 Â 4) superstructure. 108 3.6 HeSE: a unique tool for studying surface dynamics Helium spin-echo (HeSE) is a recent variation on the HAS technique 109,110 which adds manipulation of the helium wavepackets using the nuclear spin of 3 He atoms, to enable dynamical measurements to be obtained in a completely different way. Essentially, each helium wavepacket is split into two spin-components, which are separated by a time, t SE , using a magnetic field, before they scatter in turn from the surface being studied.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%
See 2 more Smart Citations
“…107 In a study of highly proton-ordered water structures on oxygen pre-covered Ru(0001) it could be shown that the atomic oxygen and the oxygen from water form a (2 Â 2) surface reconstruction, which however, is broken by the hydrogen to give a (2 Â 4) surface reconstruction: while LEED measured a (2 Â 2), HAS measured a (2 Â 4) superstructure. 108 3.6 HeSE: a unique tool for studying surface dynamics Helium spin-echo (HeSE) is a recent variation on the HAS technique 109,110 which adds manipulation of the helium wavepackets using the nuclear spin of 3 He atoms, to enable dynamical measurements to be obtained in a completely different way. Essentially, each helium wavepacket is split into two spin-components, which are separated by a time, t SE , using a magnetic field, before they scatter in turn from the surface being studied.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%
“…The top inset shows a typical measurement with the linewidth caused by a small Doppler broadening upon scattering from moving adsorbates and thus corresponding to the timescale of the molecular movement. 111 Since the process is based on self-interference of each 3 He atom, the polarisation loss depends only on the change in energy and not the beam energy itself. 109 Fig.…”
Section: Nanoscale Surface Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. [29] the diffuse scattered intensity (that accompanies the specular reflection) coming from lateral scattering length density fluctuations with intensity:…”
Section: Principles Of Grazing Incidence Scatteringmentioning
confidence: 99%
“…In the last decade, in-situ and operando Small-Angle X-Ray Scattering (SAXS), either in transmission or grazing incidence geometries, has become a very powerful tool for the characterization of nanoscale phenomena during material preparation and processing as well as on working devices [22, 23] with a time resolution in the millisecond regime [24]. These experiments have facilitated a deeper understanding of, e.g., the underlying kinetics of drying colloidal droplets [25, 26] and nanoparticle formation [27, 28], the morphological evolution during thin film preparation and processing [2932] or the correlation between polymer solar cell efficiencies and morphology [33].…”
Section: Introductionmentioning
confidence: 99%